Development of real-time energy metering bypass and remote reporting system for registered consumers - Francis Victor; Kufre Esenowo Jack; Justice Chikezie Anunuso; Kehinde Bello; Lanre Olatomiwa; Kenndey Omokere Oghenekaro (Institute of Advanced Engineering and Science, 2023)
Every economy is driven by energy supply, the quantity of energy produced, transmitted, and distributed needs to be paid for by consumers. This leads to a pay-as-you-go metering system. Paying for every energy unit used helps the energy company to improve its quality delivery. Most developing countries around the globe have not attended to their profit margin even with the introduction of the pay-as-you-go metering system. Given that some local energy users seem to bypass the metering system, thereby accessing energy without passing through the metering system, this usually hampers the productivity of the distribution companies and results in a huge revenue loss. To address this issue, this research presents a real-time energy bypass and remote reporting model to detect metering bypass from registered consumers. An inspectorate metering system was incorporated in the energy supply line to compare the amount of current-voltage supplied to consumers against the amount being utilized by the consumers to achieve the detection and reporting of the metering bypass incident by registered consumers. As a result, a signal is sent to the energy company through a remote server and the incident of the metering bypass would be displayed on a monitoring dashboard in case of disparity between the inspectorate and consumer metering system.